Optimal placement and sizing of multiple STATCOM in distribution system to improve voltage profile - Moghbel, Moayed; Masoum, Mohammad Sherkat; Deilami, Sara (2016)
Power quality is an important issue when integrating renewable distributed generations and power electronic devices in distribution systems. Possible issues are unacceptable voltage fluctuation and harmonic current injections that may result in unstable and unreliable power networks. Voltage profile can be improved by compensating reactive power using flexible AC transmission systems (FACTSs) such as the static synchronous compensator (STATCOM) which has gained wide attention due to its prodigious performance. The main objectives of this paper are placement and sizing of STATCOM units as well as evaluating their performances using particle swarm optimization (PSO) to improve voltage profiles of highly distorted distribution systems. The 15-bus unbalanced test system is used for the analyses and simulations. A five level neutral-point clamped (FL-NPC) inverter with an adaptive hysteresis current controller (AHCC) is used to model the STATCOM in Matlab/Simulink.